Nitrogen diffusion in niobium under low pressure - Souza, Armando Cirilo de; Florêncio, Odila; Grandini, Carlos Roberto [UNESP] (Trans Tech Publications, 2014)
The interaction among heavy interstitial atoms present in metals with bcc structure is studied using anelastic spectroscopy. This technique makes it possible to obtain information on interstitial concentration, precipitation, solubility limit, and diffusion. The diffusion coefficients of nitrogen in niobium were obtained using the relaxation parameters obtained from anelastic spectroscopy measurements for different oscillation frequencies of the system. The results showed the interstitial diffusion of nitrogen present in solid solution in niobium when submitted to different charges of nitrogen at a temperature of 1373 K and a partial pressure in the order of 10-4 Torr. The exponential variation of the pressure experimentally in function of the time was thus obtained.
Keywords: Diffusion; Niobium; Nitrogen